2016
DOI: 10.1038/srep27651
|View full text |Cite
|
Sign up to set email alerts
|

High-energy proton imaging for biomedical applications

Abstract: The charged particle community is looking for techniques exploiting proton interactions instead of X-ray absorption for creating images of human tissue. Due to multiple Coulomb scattering inside the measured object it has shown to be highly non-trivial to achieve sufficient spatial resolution. We present imaging of biological tissue with a proton microscope. This device relies on magnetic optics, distinguishing it from most published proton imaging methods. For these methods reducing the data acquisition time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Although the challenge of combining PT with MRI may be greater for particles than for photons, studies have shown the feasibility of a such combination [Hartman et al, 2015]. In addition, it was shown that particles could be used for imaging purposes as well, opening a wide field of new possibilities for PT [Prall et al, 2016a].…”
Section: Discussionmentioning
confidence: 99%
“…Although the challenge of combining PT with MRI may be greater for particles than for photons, studies have shown the feasibility of a such combination [Hartman et al, 2015]. In addition, it was shown that particles could be used for imaging purposes as well, opening a wide field of new possibilities for PT [Prall et al, 2016a].…”
Section: Discussionmentioning
confidence: 99%
“…The latter effect can be enhanced by the use of different proton energies for the imaging. Highly sophisticated proton radiography methods such as proton microscopy [8] or particle tracking [9,10] yield image resolutions that can compete with conventional X-ray imaging but are technically demanding. The presented imaging method, on the other hand, respects the need for practicability and mobility as well as low image acquisition dose that results from fractionated animal irradiation at proton beamlines without a permanently installed, dedicated imaging setup.…”
Section: Introductionmentioning
confidence: 99%
“…The most overlapping energy region is between 120 and 190 MeVexperiments at this energy can be done at all of the partner centers. The highest possible energies can be achieved at GSI, reaching up to 1 GeV/u for heavy ions and 4.5 GeV/u for protons, with relevance to proton radiography [40] experiments, while most of the other institutes are limited to a maximum of 230-240 MeV/u. The lowest possible proton energies are offered at the research facility of UMCG (15 MeV) and Institut Curie (20 MeV).…”
Section: Physics -Location Beamlines Particles Energies and Fieldsmentioning
confidence: 99%